THE EFFECT OF LEADERSHIP STYLE, ORGANIZATIONAL CULTURE AND WORK STRESS ON EMPLOYEE PERFORMANCE IN THE MANUFACTURING INDUSTRY - Tionom Nainggolan; Tibrani; Rona Tanjung; Hanafi Siregar (CV. Radja Publika, 2026)
This study aims to examine the influence of leadership, organizational culture, and work stress on employee performance in a manufacturing company. In the context of global competition, manufacturing companies face significant challenges in maintaining and improving employee performance. Inspiring and motivating transformational leadership, a positive organizational culture, and high work motivation are key factors in achieving these goals. This study used a quantitative approach with a survey method of 200 employees in a manufacturing company in Indonesia. The results show that these three variables have a positive and significant influence on employee performance. These findings provide practical implications for managers and company leaders in developing strategies to improve employee performance and achieve long-term success.